AI and immersive technologies in international STEM learning - Siddiqi, Muddassir (American Journal of STEM Education, 2025)
AI-powered immersive technologies, including virtual and augmented reality, reshape international STEM education by providing equitable, location-independent access to experiential learning and intercultural collaboration. This article examines their pedagogical value, implementation challenges, and strategies for fostering global engagement in STEM disciplines.